Erythroid/myeloid progenitors and hematopoietic stem cells originate from distinct populations of endothelial cells - Chen, Michael J. (2011)
Hematopoietic stem cells (HSC) and an earlier wave of definitive erythroid/myeloid progenitors (EMPs) differentiate from hemogenic endothelial cells in the conceptus. EMPs can be generated in vitro from embryonic or induced pluripotent stem cells, but efforts to produce HSCs have largely failed. The formation of both EMPs and HSCs requires the transcription factor Runx1 and its non-DNA binding partner core binding factor β(CBFβ). Here we show that the requirements for CBFβ in EMP and HSC formation in the conceptus are temporally and spatially distinct. Pan-endothelial expression of CBFβ in Tek-expressing cells was sufficient for EMP formation, but was not adequate for HSC formation. Expression of CBFβ in Ly6a-expressing cells, on the other hand, was sufficient for HSC but not EMP formation. The data indicate that EMPs and HSCs differentiate from distinct populations of hemogenic endothelial cells, with Ly6a expression specifically marking the HSC-generating hemogenic endothelium.